Management and the Environment - Meyer, G. Dale (Academy of Management Journal, 1971)
This article reviews several books, including “Environmental Quality in a Growing Economy,” edited by Henry Jarrett, “Environment: A Challenge to Modern Society,” by Lynton Keith Caldwell, and “Bus...